Ontario Baptists and the War of 1812 - Heath, Gordon (Ontario History, 2011)
This paper examines both the impact of the War of 1812 on the Baptist churches in Ontario, as well as on the response of Baptists to the war. To be sure, the war had wrought devastation upon Upper Canadian churches, and Baptist churches were no exception in this regard. All Baptists were isolated from their American colleagues, friends, and support. Upper Canadian Baptists had suffered even more through the ignominy of disloyal pastors, and the closure of churches. There may have been a purging of Americans from the Methodists of Upper Canada, but there does not seem to be the same happening among the Baptists. No doubt the desperate need among Upper Canadian Baptists for American help was a factor in this willingness to have American missionaries return. The most passionate loyalty expressed in the evidence that remains was a cross-border ecumenism that speaks to the power of the evangelical impulse. Once the war ended, the churches could quickly reopen relations and get back to the work of the church.